Optimal normal form database development for cooperative systems - Pornphol, Putsadee; Naveevong, Chantinee; Chitayasothorn, Suphamit (My University, 2017)
Currently, information technology has gained interests in various ways and has been used by almost all businesses The development of information technology has affected wider areas in every industry, both private and public Information systems are beneficial to the management of the organization or agency They allow users in each level to access information and use that information quickly, allow executives to use data from the information systems in strategic management of the organization correctly, help in the monitoring and controlling of the operation clearly and accurately, help analyze and fix problems that occur, and reduce costs and working time It can be concluded that any agency or organization that makes use of information systems in the operation and management at each level of the organization is moving in the right direction However, the information systems must be based on the development of systems that are accurate, reliable, and on the cutting edge of technology Saving and credit cooperative is another kind of agency that emphasizes on service and management by information systems, since the operation needs accurate information and cannot tolerate database update anomalies, because it is a system that is related to financial management. Information systems that have been used are either developed specifically for particular organizations or as a software package The database for the system must have the best structure and integrity constraints clearly modelled on a conceptual schema Since the use of the Entity Relationship Model ER Model cannot always guarantee the fifth normal form 5NF relational database schema, another conceptual schema model is required The NIAMORM Nijjsens Information Analysis Methodology Object Role Model which guarantee the Optimal Normal Form ONF is used instead The ONF is defined as the 5NF which has the smallest number of tables.
Keywords: 5NF; Cooperative; Information system development; NIAM